Adolescent health contemporary trends in the world and Kyrgyzstan - Mairam K. Koshukeeva; Vladimir P. Alekseev (Heart Vessels and Transplantation)
Objective: The article presents a review of foreign and domestic literature on relevant health problems and risk factors for adolescent diseases.